Manajemen Strategik Dalam Meningkatkan Mutu Kinerja Di Lembaga Pendidikan Islam - H Mahmud (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2020)
Strategic management is a series of decisions and fundamental actions made by top management and implemented by all levels of an organization in order to achieve organizational goals. Quality of performance is the quality of the work achieved in completing responsibilities in accordance with the objectives to be achieved. Characteristics of quality human resources in the era of industrialization and globalization is to have the ability: initiative, cooperation, training, assessment, communication, reasoning, problem solving, decision making, use of information, planning, learning skills, and multicultural skills. The strategy of the government through the Ministry of Religious Affairs of the Republic of Indonesia in improving the quality of educators and madrasah education personnel in the form of: a) Increased competence of PTK, MI, MTs, MA and MAK, b) Improvement of qualifications S1 madrasah teachers, c) Provision of functional allowances, professional allowances and special allowances Non-civil service PTK, d) participation of Madrasah teachers in Teacher Professional Education, e) Madrasah teacher certification, and others. The development and improvement of institutional quality must be supported by adequate facilities and infrastructures such as internet network, web-site access, e-learning for students and teachers / lecturers of study center, sport center, and others. There are three strategies for achieving superior organizational performance: a) Comparative Strategy, b) Competitive Strategy, c) Alliances Strategy. Development of human resources can be done through: 1) training, 2) developmen), 3) career development, and 4) apprasial performance. Keywords: Strategic Management, Quality of Performance, Islamic Education